Genetic and path analysis of agronomic traits in Indonesian sorghum genotypes - MUHAMAD ARIF NASUTION; ZULKIFLI MAULANA; MIR ALAM; HANAFI HANAFI; FACHIRAH ULFA; ANGRIANA ABDULLAH (Society for Indonesian Biodiversity, 2025)
Abstract. Nasution MA, Maulana Z, Alam M, Hanafi, Ulfa F, Abdullah A. 2025. Genetic and path analysis of agronomic traits in Indonesian sorghum genotypes. Biodiversitas 26: 5944-5954. Sorghum (Sorghum bicolor) is a strategic cereal for food, feed, and bioenergy in tropical production systems, yet its improvement is constrained by limited characterization of genetic variability and yield-determining traits across local and commercial germplasms. This study evaluated eight contrasting genotypes under a randomized block design in Maros, South Sulawesi, to quantify genetic variation, heritability, and trait-yield relationships. Wide phenotypic divergence was observed, with grain yield ranging from 4.64 to 58.93 g per plant and plant height from 145.6 to 265.9 cm, reflecting substantial heterogeneity within the tested germplasm. High heritability estimates for grain yield (0.75), panicle dry weight (0.75), and thousand-grain weight (0.89) indicate strong additive genetic control and substantial prospects for early generation selection. Path analysis identified thousand-grain weight (direct effect = 0.713), panicle dry weight (0.442), and panicle width (0.304) as the major determinants of grain yield, confirming the central role of reproductive biomass in yield formation. In contrast, the number of nodes and leaves exhibited negative associations with grain yield, demonstrating a physiological trade-off between vegetative vigor and reproductive partitioning, which is consistent with earlier reports across cereals. Sugar content showed moderate heritability (0.68) and a limited direct influence on grain yield, reaffirming its relevance primarily for sweet sorghum improvement. Commercial varieties (Numbu, Kawali, and UPCA-S1) exhibited superior reproductive performance, whereas local genotypes (Watasolok and Okin) expressed adaptive attributes, including taller architecture and enhanced vegetative robustness. The complementary strengths of these groups underscore the potential of targeted hybridization coupled with selection for panicle- and seed-related traits to accelerate the development of high-yielding, climate-resilient sorghum cultivars in tropical environments.